Atenção Pré-Natal: percepções de adolescentes que pariram prematuramente - Marques, Tatiane Montelatto (2019)
Introduction: Adolescent pregnancy, given its repercussions on health and life, has been taken as a challenge to Public Health. One of the axes of attention is the reception of adolescents and their families in health practices. Therefore, this study turned to prenatal care under the question “How did the adolescent who gave birth prematurely perceived prenatal care received?” Objective: To analyze the perception of adolescents who gave birth prematurely about prenatal care received at public network, with attention to the nurse's place. Method: This is a descriptive study with a qualitative approach. The data collection was developed, so that this study brought the results from the interview with 11 adolescent women, mothers of premature mothers. The open interview was used to produce the data from the initial placement: Tell me about your prenatal care and what he represented to you. All interviews were recorded in audio and underwent the analytical processes of Content Analysis (AC) and Symbolic Interactionism (IS) in the thematic modality in Bardin's proposition. Results: The results brought the perception of 11 adolescent women through four thematic categories: Discovery of pregnancy and early prenatal times, Insufficient attention in prenatal care, Dismissal of family members in childbirth and birth and Welcoming of family and friends, where (5) of them started prenatal care in the first trimester of pregnancy, (4) had 6 prenatal consultations and (2) started prenatal care late in the second trimester of pregnancy, which is not recommended by the Ministry of Health. and the Prenatal and Birth Humanization Program (PHPN) which may result in a lack of information such as the partner's right to follow up on prenatal consultations and the benefits of prenatal care. The analyzes revealed barriers to dialogue between adolescents and professionals during prenatal consultations, an essential factor for humanization and comprehensiveness. Conclusion: While discussions we can point out that prenatal care mainly, when this is the adolescent issue, there are gaps in the quality of care provided, both in reception, dialogue and rights due to lack of information. Further explorations that add to this study are necessary to densify evidence that composes the challenges of prenatal care for adolescents in the Brazilian context.